2017
DOI: 10.1038/ncomms15121
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Ms2 encodes for an orphan protein that confers male sterility in grass species

Abstract: Male sterility is a valuable trait for plant breeding and hybrid seed production. The dominant male-sterile gene Ms2 in common wheat has facilitated the release of hundreds of breeding lines and cultivars in China. Here, we describe the map-based cloning of the Ms2 gene and show that Ms2 confers male sterility in wheat, barley and Brachypodium. MS2 appears as an orphan gene within the Triticinae and expression of Ms2 in anthers is associated with insertion of a retroelement into the promoter. The cloning of Ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 50 publications
(62 reference statements)
0
67
0
Order By: Relevance
“…Which is part of a suite of stable genic male sterility (GMS) loci ( MS1–MS5 ) identified thus far in wheat (Driscoll, ; Fossati & Ingold, ; Pugsley & Oram, ; Sasakuma, Maan, & Williams, ; Zhou, Wang, Feng, Ji, & Wang, ), the five mutants identified contained ms1 and ms5 which are recessive mutants (Klindworth, Williams, & Maan, ; Sasakuma et al, ), and Ms2 , Ms3 , and Ms4 which are dominant mutants (Maan, Carlson, Williams, & Yang, ; Maan & Kianian, ; Qi & Gill, ). Currently, only one dominant gene, Ms2 , and one recessive mutant have been cloned in wheat (Ni et al, ; Tucker, Baumann, & Kouidri, ; Wang et al, ; Xia et al, ), with Ms2 mutants being widely used for wheat breeding and potentially for hybrid wheat breeding (Ni et al, ). Other genes involved in male sterility in wheat include the genes Ms26 and Ms45 which are involved in the formation of the pollen cell wall similar to ms1 which is a transcription factor and regulates the post‐meiotic development of the anther (Dong et al, ; Singh, Kumar, Thilges, Cho, & Cigan, ; Tucker et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Which is part of a suite of stable genic male sterility (GMS) loci ( MS1–MS5 ) identified thus far in wheat (Driscoll, ; Fossati & Ingold, ; Pugsley & Oram, ; Sasakuma, Maan, & Williams, ; Zhou, Wang, Feng, Ji, & Wang, ), the five mutants identified contained ms1 and ms5 which are recessive mutants (Klindworth, Williams, & Maan, ; Sasakuma et al, ), and Ms2 , Ms3 , and Ms4 which are dominant mutants (Maan, Carlson, Williams, & Yang, ; Maan & Kianian, ; Qi & Gill, ). Currently, only one dominant gene, Ms2 , and one recessive mutant have been cloned in wheat (Ni et al, ; Tucker, Baumann, & Kouidri, ; Wang et al, ; Xia et al, ), with Ms2 mutants being widely used for wheat breeding and potentially for hybrid wheat breeding (Ni et al, ). Other genes involved in male sterility in wheat include the genes Ms26 and Ms45 which are involved in the formation of the pollen cell wall similar to ms1 which is a transcription factor and regulates the post‐meiotic development of the anther (Dong et al, ; Singh, Kumar, Thilges, Cho, & Cigan, ; Tucker et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few plant orphan genes have been studied in depth. Recent studies revealed that orphan genes are important players in key agronomic traits, including Ms2 that confers male sterility in wheat (Ni et al ., ), QQS (Qua‐Quine Starch) that regulates carbon and nitrogen partitioning across species (Li et al ., ) and TaFROG ( Triticum aestivum Fusarium Resistance Orphan Gene) that enhances wheat resistance to disease (Perochon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant male reproduction phase involves a series of developmental stages from stamen primordial meristem to pollen granule formation and pollination, where deletion or abnormality of any gene will lead to MS (Budar & Pelletier, ; Chen & Liu, ). Significant achievements have been obtained on exploring genes, the analysis of molecular mechanism and its application associated with MS in major field crops, such as rice (Chang et al, ; Fan et al, ), wheat (Ni et al, ; Xia et al, ), maize (Zhang, Wu, et al, ) and other crops. In recent years, although some achievements have been made in soybean to explore the fertility genes, their molecular mechanisms, however, detailed research and application of MS still were under progress compared with improvements in related other crops such as wheat and rice.…”
Section: Genetic Mechanism Of Male Sterility In Soybeanmentioning
confidence: 99%
“…NMS used for seed production and hybrid breeding was limited due to the inability to propagate a pure MS line for commercial hybrid seed production. With the advancement of molecular gene cloning, plant transformation and recombinant DNA approaches, researchers and breeders can efficiently develop genetically engineered MS plants (Chang et al, ; Ni et al, ; Xia et al, ; Zhang, Wu, et al, ), which could facilitate the widespread use of the NMS system in commercial crop hybrid production. In summary, plant MS provides not only a key breeding basis for heterosis utilization in crop plants, but also an important material for studying the development of floral organs or stamens (male gametophyte) along with the regulation mechanism of sterile genes (Chen & Liu, ).…”
Section: Introductionmentioning
confidence: 99%